Competence-driven engineering education: A case for T-shaped engineers and teachers - Alabadan Babatope A; Taiwo M. Samuel; Philip I. Ajewole; Oluwakemi M. Anyanwu (Institute of Advanced Engineering and Science, 2020)
The demand for engineering education and graduates is increasing daily because the current service and technological designs are unable to meet the needs of the society and the expected dramatic increase in the future. The emerging skill gap requires a shift in the type of expertise required of young professionals that will be needed to successfully lead organizations in the new economy. Researchers have identified various ‘shapes’ for the engineering professionals to make them relevant to the 21st century challenge, especially in the industry where their expertise is much needed. T-shaped professionals have skills that make them to be more preferred among others. The purpose of this paper is to present the need to upgrade engineering education curriculum to produce more T-shaped graduate engineers required in the changing industrial world. The potential benefits of T-shaped professionals to organizational performance are quite significant; hence, the demand for T-shaped professionals in knowledge-intensive, service-oriented economies is increasing. Unfortunately, the challenges associated with creating more T-shaped professionals are also significant. National regulatory bodies for engineering education in Nigeria are beginning to move towards integrated curriculum to break down discipline silos and produce T-shaped graduate engineers for the fast-changing industrial world. Service Science Management and Engineering (SSME) is an emerging discipline with over 250 programmes in 50 nations seeking to create more T-shaped professionals.